2013
DOI: 10.1186/2192-0567-3-8
|View full text |Cite
|
Sign up to set email alerts
|

Public evaluation of electricity technologies and future low-carbon portfolios in Germany and the USA

Abstract: Background: This paper aims to create insights into people's technology preferences in striving to achieve a low-carbon electricity generation system. The investigation seeks to analyze informed rather than mere opinion-based public preferences towards electricity technologies and portfolios against the background of climate mitigation options. In order to compare Germany with its strong renewable energy focus with a more fossil fuel-and nuclear-oriented country, the study presented replicates a research carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
2
43
0
Order By: Relevance
“…Developing a national pathway to achieve such system change, by exploring different potential future energy scenarios, is therefore important in determining energy policy. This is an inherently complex task and the focus of much academic and political scrutiny (for example, refs [3][4][5][6][7][8]. Most such national energy scenarios and policies derive from technical and economic assessments and evaluations, but struggle to consider other types of relevant societal values and interests [9][10][11][12][13] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a national pathway to achieve such system change, by exploring different potential future energy scenarios, is therefore important in determining energy policy. This is an inherently complex task and the focus of much academic and political scrutiny (for example, refs [3][4][5][6][7][8]. Most such national energy scenarios and policies derive from technical and economic assessments and evaluations, but struggle to consider other types of relevant societal values and interests [9][10][11][12][13] .…”
mentioning
confidence: 99%
“…This is significant because previous research has repeatedly observed the importance of context in influencing public support for, and opposition to, energy technologies and options 6,24,31 . As such, this approach focuses directly on the compromises and value trade-offs often implicit within the complex set of issues related to energy futures.…”
mentioning
confidence: 99%
“…Some recent research has begun to explore aspects of this question, either by eliciting people's judgments of portfolios of energy supply options (12)(13)(14) or of future energy scenarios for particular cities and communities (15,16). What was unique about our own project was the desire to develop engagement methodologies that would permit us to elicit a range of public attitudes and values toward energy system change for the United Kingdom as whole (i.e., encompassing simultaneous supply-and demand-side changes), and in relation to current national policy imperatives.…”
mentioning
confidence: 99%
“…Reference [5] identified and suggested some insights for the people live in Germany and USA to choose and develop low-carbon electrical power generation systems. It also presented the advantages of low-carbon initiatives and crisis with the nuclear based generation systems briefly.…”
Section: Literature Reviewmentioning
confidence: 99%